“Measuring Financial Capabilities of Individual Investors: A Systematic Review” - Papi Halder; Ram Milan (International Journal of Business and Quality Research, 2025)
Financial capabilities are crucial for individual investors when making optimal selections. Due to the significance of financial capabilities and the lack of thorough summaries in recent study on this subject, this paper tries to analyze the measurements of financial capability, contemporary developments in research methods, and theoretical viewpoint from the social perspective. In this regard, we conducted a systematic review by selecting 55 papers published between 2007 and 2025 from the Scopus database. Our study found that financial capability is a multifaceted notion and can be measured in several manners: financial literacy, financial behavior, financial education, financial knowledge, financial attitude, financial confidence, financial self-efficacy, financial socialization, financial advice, and financial access. Furthermore, we performed a co-occurrence citation analysis of keywords from existing studies to identify the most influential predictors of financial capabilities. The current review also examines the inclination to incorporate significant theoretical dimensions into the research. This comprehensive investigation will provide academics, practitioners, and institutions in commerce and management with valuable information.